Reconstruction of BLP model based on secure subject access - LIU Ke-long1; DING Li2 (Tongxin xuebao)
Through the research of the BLP model,the "secure subject access" concept was brought forward.After the reconstruction of discretionary-security property,simple-security property,*-property,a modified BLP model-BLP+ model as presented.